Type 2 immunity in the skin and lungs - Akdis, Cezmi A.; Arkwright, Peter D.; Brüggen, Marie-Charlotte; Busse, William; Gadina, Massimo; Guttman‐Yassky, Emma; Kabashima, Kenji; Mitamura, Yasutaka; Vian, Laura; Wu, Jianni; Palomares, Oscar (Allergy (Copenhagen), 2020)
There has been extensive progress in understanding the cellular and molecular mechanisms of inflammation and immune regulation in allergic diseases of the skin and lungs during the last few years. Asthma and atopic dermatitis (AD) are typical diseases of type 2 immune responses. interleukin (IL)‐25, IL‐33, and thymic stromal lymphopoietin are essential cytokines of epithelial cells that are activated by allergens, pollutants, viruses, bacteria, and toxins that derive type 2 responses. Th2 cells and innate lymphoid cells (ILC) produce and secrete type 2 cytokines such as IL‐4, IL‐5, IL‐9, and IL‐13. IL‐4 and IL‐13 activate B cells to class‐switch to IgE and also play a role in T‐cell and eosinophil migration to allergic inflammatory tissues. IL‐13 contributes to maturation, activation, nitric oxide production and differentiation of epithelia, production of mucus as well as smooth muscle contraction, and extracellular matrix generation. IL‐4 and IL‐13 open tight junction barrier and cause barrier leakiness in the skin and lungs. IL‐5 acts on activation, recruitment, and survival of eosinophils. IL‐9 contributes to general allergic phenotype by enhancing all of the aspects, such as IgE and eosinophilia. Type 2 ILC contribute to inflammation in AD and asthma by enhancing the activity of Th2 cells, eosinophils, and their cytokines. Currently, five biologics are licensed to suppress type 2 inflammation via IgE, IL‐5 and its receptor, and IL‐4 receptor alpha. Some patients with severe atopic disease have little evidence of type 2 hyperactivity and do not respond to biologics which target this pathway. Studies in responder and nonresponder patients demonstrate the complexity of these diseases. In addition, primary immune deficiency diseases related to T‐cell maturation, regulatory T‐cell development, and T‐cell signaling, such as Omenn syndrome, severe combined immune deficiencies, immunodysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome, and DOCK8, STAT3, and CARD11 deficiencies, help in our understanding of the importance and redundancy of various type 2 immune components. The present review aims to highlight recent advances in type 2 immunity and discuss the cellular sources, targets, and roles of type 2 mechanisms in asthma and AD.